How vulnerable is Cali's food system to climate shocks? A historical perspective - Hurtado Bermudez, Leidy Johanna; Achicanoy Estrella, Harold Armando; Rankin-Cortázar, Sara (2021)
Two of the main effects on the supply system of a city in the agricultural sector due to climatic variations in the agricultural sector are related to the reduction of food supply and the impact on food prices. Knowing how much El Niño/La Niña climatic phenomena affect the agricultural sector that supplies food to a city, municipality or country will help to plan strategies to mitigate these impacts, the fragility of food systems and the protection of the most vulnerable. In this sense, the study is interested in knowing to what degree the supply system of the city of Cali is vulnerable to this type of phenomena, a city in which 1 out of every 2 inhabitants suffers from food insecurity, 1 out of every 2 people is poor and more than 50% of the population has nutritional deficiencies.